Slow Search: Information Retrieval without Time Constraints - Teevan, Jaime; Collins-Thompson, Kevyn; White, Ryen W.; Dumais, Susan; Kim, Yubin (Proceedings of HCIR 2013, 2013)
Significant time and effort has been devoted to reducing the time between query receipt and search engine response, and for good reason. Research suggests that even slightly higher retrieval latency by Web search engines can lead to dramatic decreases in users’ perceptions of result quality and engagement with the search results. While users have come to expect rapid responses from search engines, recent advances in our understanding of how people find information suggest that there are scenarios where a search engine could take significantly longer than a fraction of a second to return relevant content. This raises the important question: What would search look like if search engines were not constrained by existing expectations for speed? In this paper, we explore slow search, a class of search where traditional speed requirements are relaxed in favor of a high quality search experience. Via large-scale log analysis and user surveys, we examine how individuals value time when searching. We confirm that speed is important, but also show that there are many search situations where result quality is more important. This highlights intriguing opportunities for search systems to support new search experiences with high quality result content that takes time to identify. Slow search has the potential to change the search experience as we know it.